AUDIT ENERGI KONSUMSI LISTRIK DI HOTEL ASTON MANADO TAHUN 2023 - Darise, Refly J.; Maluegha, Benny L.; Rembet, Michael E. (Jurnal Tekno Mesin, 2023)
An energy audit is a method for increasing the efficiency of energy use by evaluating energy use, measuring energy consumption used in buildings, and identifying methods of its use. This research aims to calculate the energy consumption intensity (IKE) value at the Aston Manado Hotel and identify energy saving opportunities that can be implemented at the Aston Manado Hotel. IKE calculation results show IKE in deluxe rooms, superior rooms, suite rooms, Dahlia function room, Hasoka function room, meeting room, male toilet, female toilet, restaurant, lobby, lounge, accounting office, sales executive office, employee corridor, and The guest corridor is in the very efficient energy usage category because the room's IKE is less than 8.5. On the other hand, the engineering office and HRD office IKEs are in the efficient energy use category because they are in the IKE range of 8.5 to 14. Additionally, the kitchen, security office, and laundry & house keeping IKEs are in the energy use category. which is quite efficient. This is because the IKE of these rooms is valued in the range of 14 to 18.5. Apart from that, the IKE of the receptionist room is in the wasteful category because the IKE of this room exceeds the IKE standard of 18.5. Energy saving opportunities can be made on lights and computers. The lights in the Dahlia multipurpose room, lobby, security office, and laundry & house keeping still use TL and CFL type lights. These lights can be replaced with LED lights. On the other hand, the computers in the HRD office, accounting office and sales executive office still use computers with an electrical load of 250 Watts. These computers can be replaced with energy efficient computers with a power of 65 Watts Keywords: Energy Audit, Energy Consumption Intensity, Energy Saving Opportunities ABSTRAK Audit energi adalah metode untuk meningkatkan efisiensi penggunaan energi dengan melakukan evaluasi terhadap penggunaan energi, mengukur konsumsi energi yang digunakan di dalam bangunan gedung, dan mengidentifikasi metode-metode penggunaannya. Penelitian ini bertujuan untuk menghitung nilai IKE (Intensitas Konsumsi Energi) di Hotel Aston Manado dan mengindentifikasi peluang hemat energi yang dapat diterapkan di Hotel Aston Manado. Hasil perhitungan IKE menunjukkan IKE di ruangan kamar deluxe, kamar superior, kamar suite, ruang serbaguna dahlia, ruang serbaguna hasoka, meeting room , toilet male, toilet female, restaurant, lobby, lounge, accounting office, sales executive office, koridor karyawan, dan koridor tamu berada dalam kategori penggunaan energi sangat efisien karena IKE ruangan itu bernilai kurang dari 8,5. Di lain pihak, IKE ruangan engineering office dan HRD office berada dalam kategori penggunaan energi yang efisien karena berada dalam rentang IKE 8,5 sampai dengan 14. Tambahan pula, IKE ruangan kitchen, security office, dan laundry & house keeping berada dalam kategori penggunaan energi yang cukup efisien. Ini karena IKE ruangan-ruangan tersebut bernilai dalam rentang 14 sampai dengan 18,5. Selain itu, IKE ruangan receptionist berada dalam kategori boros karena IKE ruangan ini melebihi standar IKE sebesar 18,5. Peluang penghematan energi dapat dilakukan pada lampu dan komputer. Lampu di ruangan serbaguna dahlia, lobby, security office, dan laundry & house keeping masih menggunakan lampu jenis TL dan CFL. Lampu-lampu itu dapat diganti dengan lampu LED. Di lain pihak, komputer-komputer di ruangan HRD office, accounting office, dan sales executive office masih menggunakan komputer dengan beban listrik 250 Watt. Komputer-komputer itu dapat diganti dengan komputer yang hemat energi dengan daya sebesar 65 Watt. Kata Kunci : Audit Energi, Intensitas Komsumsi Energi, Peluang Hemat Energi